Pertunjukan Solis Gitar dengan Repertoar Concerto in D Major Rv 93, Laila Canggung, dan Ephiphany (Guitar Solis Performance with Repertoire Concerto in D Major Rv 93, Laila Awkward, and Ephiphany) - Seption, Moch Faisal; Supriando, Supriando; Panggabean, Della Rosa; Andranofa, Andranofa (Musica: Journal of Music, 2023)
Artikel ini memuat tentang pertunjukan repertoar gitar dan analisis permainan karya seni musik instrumen gitar klasik dan elektrik dengan repertoar yang dipilih yaitu Concerto In D Major, Laila Canggung dan Ephiphany. Analisis yang dihadirkan berupa permainan teknik gitar klasik serta gitar elektrik seperti Tirando dan appoyando, Apergio Right Hand, Legato, Barrer, Palm Mute, Vibrato, Slide dan Bending, Form Musik, gaya dan genre, serta metode pertunjukan. Ketiga repertoar yang dipilih ditinjau dari tingkat kesulitan sebagai bentuk pencapaian dari hasil pembelajaran musik di kampus ISI PadangpanjangKata Kunci: Pertunjukan Solois; Teknik Gitar Klasik dan Elektrik; Repertoar; ConcertoABSTRACTThis article contains an repertoire show and analysis of the playing of classical and electric guitar instruments with the selected repertoire of Concerto In D Major, Laila Canggung and Ephiphany. The analysis presented is in the form of playing classical guitar and electric guitar techniques such as Tirando and appoyando, Right Hand Apergio, Legato, Barrer, Palm Mute, Vibrato, Slide and Bending, Music Form, style and genre, and performance methods. The three repertoires chosen are reviewed from the level of difficulty as a form of achievement from the results of music learning at the ISI Padangpanjang campus.Keywords: Soloist Performance; Classical and Electric Guitar Technique; Repertoire; Concerto